"It's not even the leaders out here who have any say at all in how long they're gonna have to wait": A study of waiting time, power, and acceptance. (25th August 2020) - Hansen, Lasse S
Waiting time is an exercise of power. When citizens such as welfare clients, asylum seekers, or inmates encounter the state, they experience lengthy waiting time. Their cases are often delayed; their appointments are postponed or canceled. This creates uncertainty, and studies on the lived experiences of waiting time show that this makes citizens accept that they have to wait. In this study, I argue that citizens accept that they have to wait because they believe that frontline workers have no power to reduce waiting time. I explore this through an ethnographic study of citizens on social assistance at an activation site in Denmark where they perform labor to receive their benefits. The study makes three contributions to the existing scholarship on waiting time. First, it combines observations of both frontline workers' decisions about waiting time and how citizens experience these decisions. I explore how the frontline workers make citizens wait to perform labor and leave at the end of the day. The length of waiting changes daily, and citizens are rarely informed about how long they have to wait. I observe that citizens accept the waiting time even though they associate it with frustration, demotivation, and uncertainty. Second, what engenders this acceptance is the frontline workers' tendency to deflect "blame away" from their power to impose waiting time. When they justify their decisions, they deflect blame either "upwards" (toward the rules or their management) or "downwards" (toward troublesome citizens). Third, the study shows that waiting time do not only reflect structural asymmetries between the citizens and the frontline workers. Citizens accept that they have to wait, because they build trust with the frontline workers and believe that the reduction of waiting time is beyond their control. This shows that the power of waiting time is also relationally produced.